ALGUNOS DATOS NUCLEOLARES DE LOS LINFOCITOS SANGUINEOS DE LOS LEPROSOS - GONZALEZ GUZMAN, IGNACIO (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1942)
Cell types, azurophile granules, cell-, nu- clear-, and nucleolar-volumes, nucleo-cytoplasmic ratios, and cell numbers, are described for the lymphocytes from 36 lepers Statistical analysis shows a deviation from Arneth's description of the lymphocytes o
BOL INST ESTUD MED BIOL
Keywords: DATOS, NUCLEOLARES, LINFOCITOS, SANGUINEOS, LEPROSOS; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS